Microscopic Bearing Behavior of Horizontally Loaded Vertical Plate Anchors in Sandy Soil. (10th June 2022) - Zhang, Sifeng; Wang, Yushuai; Li, Chao; Li, Qing; Yang, Dong
Abstract : Vertical plate anchors are an effective technique to enhance the stability of various structures, such as retaining walls and sheet piles. More research has been devoted to their bearing capacity and macroscopically affecting parameters, while less research can be found on their microscopic bearing behavior. In this paper, the microscopic bearing behavior of vertical plate anchors subjected to a horizontal pullout load in sandy soil was investigated with the particle flow code (PFC) based on the model test results. Results show that the larger-sized anchor plates withstand greater soil pressure and affect a broader range of soil during the pullout process. The soil not behind the anchor plate is pressed, and the pressure in front of the anchor plate increases with increasing size. The soil close to the plate anchor suffers larger pressure while the soil far away from the plate anchor is less affected, and the soil is redistributed to a more stable state during the pullout process of the plate anchor. The particles with a long axis distributed in the horizontal direction are the most stable, while those with a long axis distributed in the vertical direction are the most unstable.